Dispersal, reproductive success, and habitat use by translocated lesser prairie-chickens - Berigan, Liam Akerlof (Kansas State University, 2019)
Lesser prairie-chicken (Tympanuchus pallidicinctus) populations in the Sand Sagebrush Prairie Ecoregion have reached historic lows in the last decade. Former core areas of the ecoregion, such as the U.S. Forest Service Cimarron and Comanche National Grasslands in southwestern Kansas and southeastern Colorado, have reached population densities so low that populations will not be able to recover without a new source of birds. In an attempt to recolonize previously occupied areas in the region, Colorado Parks and Wildlife and Kansas Department of Wildlife, Parks, and Tourism translocated 411 lesser prairie-chickens to the National Grasslands between fall 2016 and spring 2019. For a translocation project to be successful, translocated birds need to stay near the release site, find habitat that meets their survival requirements, and successfully reproduce. I assessed the success of the translocation project to determine which of these requirements were met following release to meet the goal of increasing lesser prairie-chicken density on the National Grasslands and define potential obstacles for future translocation projects. I estimated nest success of lesser prairie-chickens translocated to the National Grasslands using Program MARK and determined those factors important in predicting nest success. I found that the number of years that had elapsed since the bird’s release was the best predictor of its nesting success in any given year. This fits with existing literature on grouse translocations, which state that translocation effects dissipate in years following release. Unfortunately, only 10.3% of translocated birds survived into the second year to take advantage of the increased nest success rate. My analysis of lesser prairie-chicken movement after release showed extensive dispersal away from the release site, with 99% of birds undergoing a dispersal movement >5 km from the release site. I conducted a behavioral change point analysis on translocated birds as they dispersed to determine where they settled down and how long their dispersal lasted. Birds moved an average of 144 km during their 1-2 month dispersal movement following release. Despite the presence of leks and habitat at the release sites, 69% of released birds settled >5 km from their release site after their movements. These results indicate that dispersal is an innate response to translocation, and release site placement will not be sufficient to minimize the dispersal movement.
Keywords: Lesser prairie-chicken; Dispersal; Nest survival; Translocation; National Grasslands